How green are my apples - The greenhouse gas emissions and blue water scarcity footprint of fresh apple supply chain - Hess, Tim M.; Martin, Hannah; Gage, Ewan; Falagán, Natalia (Elsevier, 2026)
The environmental impact of the UK fresh apple supply chain depends on the sourcing locations. This paper examines the contribution of production, storage, processing, and transport to evaluate the greenhouse gas emissions (GHGE) and blue water scarcity footprint of the main sources of apple supply to the UK (2016 – 2025). Domestic production accounted for 38 % of supply, with imports from the rest of Europe (e.g. France, Italy, Germany, Ireland, The Netherlands, Spain) representing for 37 % and most of the remainder from southern hemisphere countries, such as South Africa (12 %), New Zealand (7 %) and Chile (5 %). Our results revealed that GHGE at the orchard stage for UK, European, and Chilean apples are similar. During postharvest, cold storage is the main contributor for GHGE, which were 40 % lower in northern hemisphere countries compared to maritime shipping stages for the southern hemisphere areas. Transport emissions are affected by international travel distances. South Africa and Spain presented the highest blue water consumption (BWC) as well as blue water scarcity footprint. We found that blue water scarcity footprints are negligible where apple production is rainfed. The results suggest that in order to mitigate GHGE, energy mixes need to be improved as well as cold storage technologies. For water footprint, implementing infrastructural changes is paramount. These results can help as decision making tool to define new sourcing strategies that can minimise environmental impacts. This assessment also highlights limitations in methodology, including inconsistent approaches in GHGE assessment, and underscores the need for standardised methodologies, emphasises the role of externalities, and highlights the importance of considering economic and social factors in assessing environmental trade-offs in apple supply chains.
Keywords: Agronomy & Agriculture; 3002 Agriculture, land and farm management; 3004 Crop and pasture production; 4005 Civil engineering; Life Cycle Assessment; Import; Food supply chain; Food miles; Carbon footprint; United Kingdom